The Trigeminocardiac Reflex? Severe Bradycardia Secondary to Facial Trauma: A Case Report - Boris Penev; Hallmon Hughes; Katherine Scarpino; Daniel J. Ritter (Clinical Practice and Cases in Emergency Medicine)
Introduction: The trigeminocardiac reflex (TCR), a physiologic response to irritation of the branches of the trigeminal nerve, was first described in humans in 1870. Gastric hypermotility, hypotension, bradycardia, and even asystole have been reported in response to surgical manipulation of the trigeminal nerve and its branches, but literature is limited in patients not undergoing surgery. Although effects are generally transient and benign, TCR can present a significant diagnostic and therapeutic challenge in patients undergoing surgical manipulation of the trigeminal nerve and its branches. Case Report: We describe a case of severe bradycardia secondary to facial trauma causing hemodynamic compromise and diagnostic uncertainty. Conclusion: This case highlights a possible case of TCR, as well as therapeutic considerations, in a patient presenting to the emergency department with severe facial trauma.